A influência da leitura em voz alta na revisão de textos de alunos do 9º ano do ensino fundamental - Shirley Cristina Miranda (2015)
This work investigates the influence of oral reading in textual review of basic education students, checking what are the most frequent language in the rewriting operations. It is known that a teaching job, thought the light of theories of Applied Linguistics, is the first step to offer significant opportunities for the development of writing. Within this perspective, it highlights one of the key steps to this linguistic competence, namely the textual revision. The question that guides our work - properties that contribute to the textual rewriting - relates to the concern of many teachers in relation to this school writing step. One of the Portuguese language teaching objectives is precisely to equip students to be competent in their language. That is to say, among other things, to make the apprentice use their skills and expertise not only in written production, as well as rewriting your text. By bringing this concern - many teachers today - for the scope of our work, the objective is to outline the contributions of authors like Geraldi (1997, 1999, 2010), Fiad (1991, 2009) and Menegassi (1998, 2001) and sketch a work proposal focused on students' reading ability. This perspective comes from reading books Ruiz (2001, 2010) and the perception that students can view errors in their own newsrooms when they are asked to read them. Thus, it was found that the types of textual correction, prepared by the author, not enclosed in a written intervention, always starting from the teacher. In this work, the results are presented of analyzes between versions of a I cause (initial and final) produced by students from 9th grade, compared with the linguistic procedures of students during oral reading.